Surgical Treatment of Patients with Endometriosis in the Certified Endometriosis Centers of the DACH Region – A Subanalysis of the Quality Assurance Study QS ENDO pilot - Zeppernick, Felix; Zeppernick, Magdalena; Wölfler, Monika Martina; Janschek, Elisabeth; Holtmann, Laura; Bornemann, Sebastian; Oehmke, Frank; Salehin, Darius; Scheible, Chi Mi; Brandes, Iris; Vingerhagen-Pethick, Sigrid; Cornelius, Claus-Peter; Boosz, Alexander; Krämer, Bernhard; Sillem, Martin; Keckstein, Jörg; Schweppe, Karl-Werner; Meinhold-Heerlein, Ivo; for the QS ENDO Working Group of the Endometriosis Research Foundation (SEF) (Geburtshilfe und Frauenheilkunde, 2024)
Introduction After puberty, at least 10% of all women and girls suffer from endometriosis. Surgery is useful for both the diagnosis and therapy. To date, quality indicators for the surgical treatment of endometriosis are lacking. QS ENDO aims to record the quality of care provided in the DACH region and to introduce quality indicators for the diagnosis and treatment of endometriosis. In the first phase of the study, QS ENDO real, the reality of care was recorded using a questionnaire. The second phase, QS ENDO pilot, investigated the treatment of patients who underwent surgery in certified endometriosis centers in a defined time-period.Material and Methods The surgical data of 10 patients from each of the 44 endometriosis centers in the DACH region was recorded using an online tool. Collected data included the approach used, the endometriosis phenotype, a description of the surgical site, resection status, histological confirmation, the use of a classification, and any complications. All operations were carried out in October 2016 as the defined time-period. The surgical approaches used were compared with the recommendations in the current guidelines.Results The data of 435 patients with a median age of 34 years were evaluated. 315 (72.4%) were nulliparous. 120 patients had given birth to at least one child and 42.5% (51) of them had delivered their child by caesarean section. About 50% of all patients also had deep infiltrating endometriosis in addition to ovarian endometriosis, and the median NAS score was 7.5. With regards to the surgical treatment, endometriomas were completely resected in 81% (94) of patients. 87.3% of patients underwent resection of peritoneal endometriosis. Forty-one patients had a hysterectomy, with a total hysterectomy carried out in 26 (63.4%) and a supracervical hysterectomy in 15 (36.6%) patients. Of the 59 patients with bowel endometriosis, half had segmental resection and half had shaving of the anterior rectal wall. Complications requiring revision occurred in 0.9% of cases.Conclusion The surgical procedures carried out in the certified endometriosis centers of the DACH region are largely in line with the recommendations for appropriate surgical approaches in the current standard guidelines.
Keywords: quality of care; reality of care; care research; endometriosis centers; quality indicators; surgery